Nice teams finish last the secret to unleashing your team's maximum potential - Miller, Brian Cole 1956-; IG Publishing (New York American Management Association, 2010)
Don't rock the boat. Don't make waves. Don't offend anyone. There's a palpable feeling that clouds many team meetings and keeps them from being productive: over-politeness. And while the conflict that naturally exists in most organizations hasn't gone away, it manifests itself in passive aggression, mediocrity, and a molasses-like inability to get anything done. "Nice Teams Finish Last" provides the antidote to this all too common tendency, giving managers, team leaders and members, and facilitators the practical exercises and assessment tools they need to battle 'the nice trap' and start getting results! The book helps readers encourage skills such as constructive criticism, honest communication, and the kind of conflict that drives innovation and quality. From giving clear, sharp feedback, to effectively challenging others, this book provides the eye-opening tools teams need to achieve very nice results!
Nice teams are-- well, nice! -- The opposite of nice is mean, isn?t it? -- The sweet spot between nice and fierce : bold -- Bold principles -- Bold feedback -- Bold requests -- Bold disagreements -- Become bold.
Electronic reproduction.
Keywords: Teams in the workplace; Communication in organizations; Interpersonal communication; Electronic books